(8) تقييم التوجهات الاستراتيجية وأبعاد الحوكمة التشريعية والمؤسسية والتخطيطية لتعميق التصنيع المحلي في مصر Evaluation of strategic directions and the dimensions of legislative institutional and planning governance to deepen Egypt's industrialization - أ.د. محمد ماجد خشبة د. مي مصطفى عوض (معهد التخطيط القومي, 2026)
إن لاعتبارات ومتطلبات الحوكمة التخطيطية والتشريعية والمؤسسية والإجرائية دورًا محوريًا في سياسات التنمية الاقتصادية والاجتماعية والمعرفية في دول العالم المختلفة وعلى مستوى كافة القطاعات الرئيسة بما فيها القطاع الصناعي. كما تشغل هذه الاعتبارات حيزاً هاماً في العديد من التقارير العالمية والإقليمية المعنية بالتنافسية وحالة بيئات الأعمال والحوكمة وفى هذا الإطار، تبنى مشروع تعميق التصنيع المحلى بمعهد التخطيط القومي دراسة الجوانب المختلفة للأطر والممارسات التخطيطية والتشريعية والمؤسسية والتنظيمية والإجرائية، وتقييم تأثيراتها على القطاع الصناعي بوجه عام وتعميق التصنيع على وجه الخصوص. وقد طرحت الورقة تقييماتها لتلك الجوانب في أربعة محاور، تناول المحور الأول استعراض أبرز التوجهات الاستراتيجية لتعميق التصنيع في مصر، وكذلك عرض خبرات بعض الدول الناهضة والنامية للتعرف على أفضل الممارسات في هذا الشأن وعلى الأخص ما يتعلق منها بمقومات بناء سياسة صناعية وطنية مستدامة. وتناول المحور الثاني من الورقة التوصيف الشامل لبيئة الحوكمة التشريعية والمؤسسية والتخطيطية ذات الصلة بالصناعة بوجه عام وتعميق التصنيع على وجه الخصوص في مصر، ورصد وتحليل الفجوات الحاكمة في هذا الخصوص والمتعلقة بتقادم أو نقص التشريعات، والتضخم المؤسسي وتداخل الأدوار المؤسسية، وفجوات في التوجهات والسياسات الفعالة لتعميق التصنيع، ومدى قابلية تحويل هذه السياسات إلى مشروعات وبرامج ومبادرات قابلة للتقييم والمراجعة لدعم التنمية المستدامة. ولخص المحور الثالث للورقة أهم الخبرات المستفادة من المراجعات التخطيطية والتشريعية والمؤسسية ذات الصلة بتعميق التصنيع في مصر. وفى ضوء المراجعات والتقييمات السابق الإشارة اليها، طرحت الورقة في المحور الأخير تصورًا عمليًا لمنظومة جديدة متكاملة لإدارة وحوكمة التخطيط وصنع السياسات الصناعية وتعميق التصنيع في مصر، مع تقديم مقترحات لسد بعض الفجوات التشريعية والمؤسسية والإجرائية الكفيلة بتفعيل أدوار هذه المنظومة المقترحة. وتتضمن هذه المنظومة إنشاء كيان مؤسسي جديد تحت مسمى المجلس الصناعي المصري. يرتبط هذا الكيان بجهاز التخطيط الوطني، وينهض بأعباء الأدوار التخطيطية والتنسيقية والاستشارية والتحفيزية المعنية بصنع ومتابعة وتقييم السياسات الصناعية المستدامة وتعميق التصنيع في مصر. ويضم المجلس فى عضويته كافة الأطراف الحكومية وغير الحكومية المعنية بقضايا الصناعة وتعميق التصنيع في مصر، بما فيها الوزارات والأجهزة المعنية، بالإضافة إلى التنظيمات المهنية والنقابات العمالية، ومراكز ومعاهد البحوث والفكر. كلمات مفتاحية: خبرات مصرية ودولية- الحوكمة- المجلس الصناعي المصري The planning, legislative, institutional and procedural governance considerations and requirements play a pivotal role in economic, social and knowledge development policies in various countries of the world and at the level of all major sectors, including the industrial sector. These considerations also occupy an important place in many global and regional reports on competitiveness, the state of doing business environments, and the state of governance. In this context, the project of deepening local industrialization at the Institute of National Planning (INP) seeks to study various aspects of planning, legislative, institutional, organizational, and procedural frameworks and practices, and to assess their effects on the industrial sector in general and on deepening industrialization in particular. The paper presented its evaluations of these aspects in four axes. The first axis dealt with reviewing the most prominent strategic directions for deepening industrialization in Egypt, as well as presenting the experiences of some emerging and developing countries in order to identify best practices in this regard, especially those related to the elements of building a sustainable national industrial policy. The second axis of the paper dealt with a comprehensive description of the legislative, institutional, and planning governance environment related to the industry in general and deepening industrialization in particular in Egypt, monitoring and analyzing the ruling gaps in this regard related to the obsolescence or lack of legislation, institutional inflation and overlapping of institutional roles, gaps in effective trends and policies to deepen Industrialization, and the extent to which these policies can be transformed into projects, programs and initiatives that can be evaluated and reviewed to support sustainable development. The third axis of the paper summarized the most important experiences learned from the planning, legislative and institutional reviews related to deepening industrialization in Egypt. In light of the previous reviews and evaluations referred to, the paper suggested in the last axis a new integrated system for managing and governing planning, industrial policy-making and deepening industrialization..The proposed system includes a new institutional entity named the Egyptian Industrial Council. This entity is linked to the National Planning Authority, and assumes the planning, coordination, advisory and motivational roles concerned with making, monitoring and evaluating sustainable industrial policies and deepening industrialization. The council includes in its membership all governmental and non-governmental parties concerned with industrial issues and deepening industrialization, including the relevant ministries and agencies, in addition to professional organizations, labor unions, and research and think tank centers and research institutes. Keywords: Egyptian and international experiences-Governance-The Egyptian Industrial Council.